“You Ought to Play Football!” Football Terminology in the Literary Works by Yurii Smolych as Representation of the Ukrainian Football Discourse in the Naddniprianshchna Regional Lexicon in the First Half of the ХХth Century (Linguostylistic Studies, 2019)
Diachronic analysis of the football terminology creation in the Ukrainian language does not only allow reviewing its functioning in special contexts which are usual for this layer of vocabulary, but also provides a basis for determining the use of the football nominations in the literary texts. Yurii Smolych is practically the only writer from Naddniprianshchyna region of the interwar period who touched on the football topic in his literary works. That is why the review of his texts is very important for clarifying the specificity of the Ukrainian football nominations development in the Naddniprianshchyna region. The main goal of the research is the analysis of the selected football lexicon from the literary works by Yurii Smolych. Comparison of it with special football nominations which functioned for naming the same football notions in Halychyna before World War II can provide further opportunities for tracing peculiarities of the Ukrainian football discourse in Naddniprianshchyna in the first half of the ХХ century.The analysis of the Ukrainian football vocabulary which was used in Yurii Smolych’s literary texts has revealed that the author uses extremely wide range of special football terms. The analyzed 19 groups of football nominations manifest that the foreign loanwords in names of a football game, its parts and football tournaments, names of a team and unions of teams, names of the game moments dominate. The majority of the original names concern the lines of football players on the playing field, names of fans and their actions. Both the loanwords and genuine Ukrainian nominations are the base of the groups denoting names of football uniform and the results of football games and their quantitative indicators. Ukrainian lexemes and hybrid derivatives form the main part of the nominations regarding football equipment, names of football actions, variety of kicks, training activities, names regarding peculiarities of a football game, whereas foreign loanwords prevail in the nominations of football players and the names of a football field and its parts. Thus, in his literary works Yurii Smolych has involved various lexical units concerning the most important thematic groups of football lexicon in which loanwords and hybrid nominations prevail. It is characteristic of the football discourse in Naddniprianshchyna, unlike the football language in Halychyna, where genuine Ukrainian nominations prevailed over loanwords in the first half of the ХХ century. Key words: Ukrainian football discourse, Yurii Smolych, literary text, football terminology, thematic groups of football names. SourcesSmolych, Yurii. «Nashi tainy». Smolych, Yurii. Dytynstvo; Nashi tainy; Visimnadtsiatylitni. Kyiv : Naukova dumka, 1987, pp. 136–377.Smolych, Yurii. «Ia vybyraiu literaturu». Smolych Yu. Tvory. 6 vols. Vol. 6. Kyiv, 1973, pp. 582–602. ReferencesProtsyk, Iryna. ““Football Teaches to Defend and Gain”: Thematic Classification of Ukrainian Football Terminology at the end of the ХІХth – Beginning of the ХХth Centuries”. Herald of L'viv Polynechnic National University “Problems of Ukrainian Terminology”, no 842, 2016, pp. 151–7.Protsyk, Iryna. ““He has become Anardent Supporter of Football for All his Life”. Ukrainian Football Terminology in Literary Works in the 30–40-ies of ХХ Century”. Zapyski z ukrains′kogo movoznavstva, iss. 24, vol. 1, 2017, pp. 318–28.Protsyk, Iryna. “Football Terminology of the 1st Half of the 20th Century in the Text”. Terminolohichnyi Visnyk, iss. 4, 2017, pp. 281–8.Struhanets, Yurii. Semantyka, struktura, funktsionuvannia futbolnoi leksyky v ukrainskii literaturnii movi pochatku XXI stolittia. PhD Thesis Abstract. Ivano-Frankivsk, 2016.Struhanets, Yurii. “Funktsionuvannia futbolnoi leksyky u khudozhnii movi”. Vitchyzniana nauka na zlami epokh: problemy ta perspektyvy rozvytku: materialy XX Vseukrainskoi naukovo-praktychnoi internet-konferentsii (30–31 Jan. 2016, Pereiaslav-Khmelnytskyi), iss. 20, 2016, pp. 122–4.